Study of service levels in Lattakia International Container Terminal LICT - صليبه سائر; ديبو علي (Latakia University Journal -Engineering Sciences Series, 2020)
Container transportation is one of the essential elements of modern ren aissance in shipping business in the world. Due to its extremely important, most countries have focused (especially the developed ones) on development of their maritime fleets and ports, in order to be able to keep up and keep the remarkable development and extremely rapid progress in containerization technology. Port capabilities should be commensurate with the developments in maritime transport fleets and their transport patterns represented by container vessels that require advanced port services such as high efficiency of workers and cranes, and modern and fast performance specialized equipments, and modern electronic systems. The study addressed the basic criteria for the level of services in the container terminals that have been identified in the United Nations Conference on Trade and Development UNICTAD 2012, These criteria were applied to Lattakia International Container Terminal (LICT), where the relative waiting time and productivity coefficient (P) were calculated for the duration of the ship’s stay in the port, and the statistical indicators of the times of ships at the Lattakia International Container Terminal and the container handling rates was studied during the period Extending from 2014 to 2017, The study concluded that the average wait time relative achieved the value of 0.0553, which put it at level B which is the second level of four levels, A, B, C, D, in addition to the level B is also achieved by productivity coefficient (P) and the value of 54.4 during the The study period.